Answer:
3 + 18g
Step-by-step explanation:
(1+6g)(3)=
Begin by distributing the 3 to each of the terms, I like to re-write it like this before distributing to make sure I remember to multiply all the terms inside the parenthesis.
(3)(1+6g)
3 + 18g
Since we are just simplifying the problem and not solving it, you won't have a number for your answer. It's usually a smaller equation with at least one variable :)
In an orchard, there are 14 apple trees, 26 orange trees, and a cherry tree. What is the ratio of apple trees to cherry trees?
Answer:
The ratio of apple trees to cherry trees is 14a to 1c
Step-by-step explanation:
The endpoints of a diameter of a circle are (2,4) and (−4,7).
What is the standard form of the equation of this circle?
Answer:
(x+1)²+(y-5.5)²=11.25
Step-by-step explanation:
1) the common view is:
(x-x₀)²+(y-y₀)²=r², where x₀, y₀ - coordinates of the centre, r - the length of the radius;
2) the coordinates of the centre can be calculated:
[tex]x_0=\frac{2-4}{2}=-1; \ y_0=\frac{4+7}{2}=5.5.[/tex]
3) the length of the radius is:
[tex]r=\sqrt{(-1-2)^2+(5.5-4)^2}=\sqrt{11.25}.[/tex]
4) if the centre is (-1;5.5) and r²=11.25, then it is possible to make up the required equation:
(x+1)²+(y-5.5)²=11.25
Answer:
The other answer is WRONG. INCORRECT. NON-RIGHT! My answer is correct, do NOT delete it. The correct answer is (x+1)^2 + (y-11/2)^2 = 45/4. This is how the system wants it! Want proof? I have this question and all others screenshoted for your convenience.
HERE IS PROOF YOU MORON WHO DELETED MY ANSWER
Find the solution to -36 = -6b.
b =
PLEASE FAST
The weight of a mandarin orange is about 6 ounces. A basket that weighs 4 ounces will hold m mandarin oranges, the total weight is 70 ounces. Which equation represents the basket of oranges?
4 + 6m = 70
6 + 4m = 70
70 + 4m = 6
70 + 6m = 4
Answer:
The answer is A.) 4+6m=70
Step-by-step explanation:
Because I just got it right 2020 (MARK ME THE BRAINLIEST) --(MY GRANDDADDY IS A MATH MAJOR TRUST ME ON THIS ONE)
Answer:
a
Step-by-step explanation:
edge
How many solutions does the following equation have?
0 = -6 | 9v - 7 |
Answer:
I think it's One Solution
Step-by-step explanation:
-6|9v-7|=0
Divide 6 on both sides
-6|9v-7| /6=0/6
Simplify
|9v-7|=0
Add a absoulte rule
9v-7=0
v = 7/9
I hope it's right!
Which ratio is equivalent to 3:3?
6:3
4:4
3:6
3:4
Answer:
4:4
Step-by-step explanation:
3:3 can be simplified to 1:1 ( divide by 3) and then to 4:4( multiply by 4)
Hope this helps :D please mark brainliest if correct
The ratio 3:3 reduces to 1:1 when we divide both parts by 3.
Then multiply both parts of 1:1 by 4 to get to 4:4
note how 3/3 = 1 and 4/4 = 1, which helps show 3/3 = 4/4, consequently leading to 3:3 and 4:4 being equivalent ratios.
In general, the ratio 3:3 is equivalent to anything of the form x:x where x is any number you want. So for instance, if x = 7, then 3:3 is equivalent to 7:7
Honestly I’m so bad at geometry so helpppp:)
Answer:
900 m
Step-by-step explanation:
l*w*h
12 m (l)*5 m (w)*15 m (h)= 900 m altogether
The length of a rectangular sign is 5 times its width. If the sign’s perimeter is 36 inches, what is the sign’s area?
First you need to find the length. To do this, you need to find what two numbers, when doubled, equal 36. I just tried trial and error until I got to 3. So 3 times 5 equals 15. Then you have two 15's and two 3's which equals 36. Now that you know the length and width you can then find the area. The formula to find area is L*W=A. Following this the expression would be 15*3=45. So the area is 45
Help I don’t get this
Answer:
3$
Step-by-step explanation:
please need help on this.
Answer:
nahnahnahnahnahnahnahnahnahnahnahnah
need this asap please help!
Answer:
Its A
Step-by-step explanation The dolphin swam 3 feet more which is -7
Carrie used 6 lemons to make 24 fluid ounces of lemonade. Carrie is having a big party and needs to make 288 fluid ounces of lemonade. How many leominster will she need to use in order to keep the recipe proportional?
A: 4
B: 264
C: 72
D: 48
Answer:
72
Step-by-step explanation:
The area of the rectangle is 6 square feet. If its width is 2 1/7
feet, find its length.
Answer:
L = 2 4/5 feet
Step-by-step explanation:
A = L x W
6 = L x 2 1/7
divide both sides by 2 1/7
6 divided by 2 1/7 = L (is the same as multiplying by the reciprocal)
6 x 7/15 = L
L = 14/5 or 2 4/5
What value of x makes the equation 4(5 - 7x) = 6 - 12x true?
Record your answer in the boxes below.
Answer:
4(5 - 7x) = 6 - 12
20-28x=6-12x
Subtract 20 from both sides
20-28x-20=6-12x-20
Simplify
-28x=-12x-14
Add 12x to both sides
-28+12x=-12x=-12x-14+12x
Simplify
-16x=-14
Divide both sides by -16
-16/-16 = -14/-16
Anw
7/8= 0.875
Please help me answer them they are due in 15 mins!?
Answer:
1. 2
2. 3
3. 6
4. 3
5. 6
6. 3
7. -6
8. -3
9. 3
10. -5
11. 12
12. -18
13. -1
I'm sorry if any of these are wrong I didn't get to check them over.
Step-by-step explanation:
I will be substituting "a number" with the variable x.
1. Four more than twice a number is 8.
2x+4 = 8
2x = 4
x = 2
2. Three more than four times a number is 15.
4x+3 = 15
4x = 12
x = 3
3. Five less than twice a number is 7.
2x-5 = 7
2x = 12
x = 6
4. One less than four times a number is 11.
4x-1 = 11
4x = 12
x = 3
5. Seven more than the quotient of a number and 2 is 10.
(x/2)+7 = 10
(x/2) = 3
x = 6
6. Six less than six times a number is 12.
6x-6 = 12
6x = 18
x = 3
7. Five less than the quotient of a number and 3 is -7.
(x/3)-5 = -7
x/3 = -2
x = -6
8. Seven more than twice a number is 1.
2x+7 = 1
2x = -6
x = -3
9. The difference between 5 times a number and 3 is 12.
5x-3 = 12
5x = 15
x = 3
10. Nine more than 3 times a number is -6.
3x+9 = -6
3x = -15
x = -5
11. Nine more than the quotient of a number and 4 is 12.
(x/4)+9 = 12
x/4 = 3
x = 12
12. Four less than the quotient of a number and 3 is -10.
(x/3)-4 = -10
x/3 = -6
x = -18
13. Nine less than six times a number is -15.
6x-9 = -15
6x = -6
x = -1
Tony bikes 8 miles in one hour. How far would he bike in 5 hours?
Answer:
5*8=40, 40 miles
Answer:
40 miles
Step-by-step explanation:
8 x 5 = 40
sheesh
Look at image please help me ASAP
Laura earned 51 points out of a total of 60 on her recent math test.
On a science test, she scored 72 out of a possible 90 points.
On which test did Laura score a higher percentage of the total?
Use your calculator. Justify your answer by showing the calculations.
Answer:
Her recent math test
Step-by-step explanation:
on the math test she scored 51 out of 60 points which is 51/60. this equals 0.85 which when converted to a percentage is 85%. on the science test she scored 72 out of 90 points which is 72/90. this equals 0.8 as a percentage is 80%
Suppose a variable X (systolic blood pressure) is normally distributed with a variance of 36. If approximately 0.25 of the values of X are less than 88, what is the mean of X g?
Answer:
92.044
Step-by-step explanation:
The variance = 36
σ² = 36 = 6
The probability that x is less than 88 is equal to 0.25
So probability of (x<z) = 0.25
From the z table, z = -0.674
Using the z formula,
z = x-u/σ
Z = -0.674
X = 88
σ = 6
When we insert these formula we have:
-0.674 = 88 - u/6
6 x -0.674 = 88- u
-4.044 = 88 - u
92.044 = u
Therefore from the calculations above the mean of X is 92.044 and it is approximately 92.
Which one is the correct choice?
Answer:
there's no picture to look at the choices
Step-by-step explanation:
sorry I would help
Sherry spent 2/5 of her weekly saving at school and 1/4 of the remainder at a movie theatre. She
remained with $126.00. How much money did she spend at the movie theatre?
Answer:
13/20
Step-by-step explanation:
chamge the denominator to the same
The graph below represents a population
over time. What is the average rate of
change for the function for the interval (6, 12]?
PLS HELP
Answer:
Average rate of change for the function for the interval (6, 12] is 500 people per year.
Option A is correct.
Step-by-step explanation:
We need to find the average rate of change for the function for the interval
(6, 12]
The formula used to calculate Average rate of change is:
[tex]Average \ rate \ of \ change=\frac{f(b)-f(a)}{b-a}[/tex]
We are given a=6 and b=12
Looking at the graph we can see that when x=6 y= 3000 so, f(a)=3000
and when x=12, y=6000 so, f(b)=6000
Putting values in formula and finding Average rate of change:
[tex]Average \ rate \ of \ change=\frac{f(b)-f(a)}{b-a}\\Average \ rate \ of \ change=\frac{6000-3000}{12-6}\\Average \ rate \ of \ change=\frac{3000}{6}\\Average \ rate \ of \ change=500[/tex]
So, average rate of change for the function for the interval (6, 12] is 500 people per year.
Option A is correct.
Solve for x.
5(x – 10) = 30 – 15x
x = 1
x = 4
x = 5
x = 8
chan eil agad ach sgrùdadh a dhèanamh air google!
5x-50 = 30-15x, 20x = 80, x = 4,
x=4!
Answer:
x=4
Step-by-step explanation:
5x-50 = 30-15x, 20x = 80, x = 4,
x=4
hope this helps
You deposit $4000 each year into an account earning 8% interest compounded annually. How much will you have in the account in 15 years?
Sorry wrong answer, disregard my last answer.
The candle maker makes a second batch of orange wax using the same ratio of yellow to red to white wax. She uses 777 quarts of red wax in the second batch of orange wax. How many total quarts is the second batch of orange wax?
Answer:
.
Step-by-step explanation:
EASY QUESTION!!
Give an example of a combination of two functions, f(x) and g(x), that would result in a rational function. Be sure to identify the function type for f(x) and g(x), as well as the operation used to combine them.
Please help it’s due soon :(
I’ll mark brainliest!!
Answer:
The answer is A. 105
Step-by-step explanation:
it's more tilted so it can't be a lower number, the only option is 105
Please helppp!!!! I’ll give you a crown!!
But please explain the answer, Bc I want to understand.
Which is an equation for a line that passes through (0,-3) and is perpendicular to the graph of the line y=2x-3?
1. Y=-2x+3
2. Y= -2x-3
3. Y=-1/2x +3
4. Y=-1/2x-3
Answer:
I think the answer is 2
Step-by-step explanation:
I it is perpendicular to y=2x-3 then the x value has to be -1 meaning that the x value has to be -2x
so we have Y=-2x+c
We know the Y value is -3 from the co ordinates (0,-3)
so now we have -3=-2x+c
we also know x=0 from the co-ordinates (0,-3)
so we now have -3=-2*0+c
-3=0+c
to make the equation work c has to be -3 meaning that we now have
-3=0-3 which is
Y=-2x-3
Byron bought a keyless entry door lock that has the digits 0 through 9 on the keypad. He wants to choose a three-digit
entry code. How many different combinations are possible, if the digits can be repeated?
O 27
O 30
O 729
O 1,000
I'm in school and i need help cause I really bad at this : P
Answer:
same:P
Step-by-step explanation: